Probing the adsorption and interaction mechanisms of hydrophobically modified polyacrylamide P(AM-NaAA-C16DMAAC) on model coal surface: Impact of salinity. (September 2019) - Zou, Wenjie; Gong, Lu; Huang, Jun; Pan, Mingfei; Lu, Zhenzhen; Sun, Chunbao; Zeng, Hongbo
Graphical abstract: Highlights: Hydrophobically modified polyacrylamide (HMPAM) was used in coal flocculation. Adsorption and adhesion of HMPAM on model coal surface increase under high salinity. HMPAM has higher affinity to model coal surface than commercial PAM. Hydrophobic interactions play an important role in the adsorption mechanism. Abstract: Selective flocculation is an efficient separation method for processing fine coal. In this work, one type of hydrophobically modified polyacrylamide, poly(AM-NaAA-C16 DMAAC) (HMPAM), was synthesized and used as flocculants of coal. The adsorption and interaction of HMPAM on model coal surface under the influence of KCl concentration were compared with a commercial polyacrylamide (PAM) using quartz crystal microbalance with dissipation monitoring (QCM-D), multi-angle laser light scattering (MALLS) and atomic force microscope (AFM). The QCM-D results showed that the adsorption amounts of both PAM and HMPAM on model coal surface increased with increasing KCl concentration, and the amount of HMPAM was much higher than that of PAM in 100 mM KCl solution. This result could be due to the fact that the high salinity (e.g., 100 mM KCl) led to the compressed conformation of the polymers and significantly compressed electric double layer repulsion. The conformational changes were determined using MALLS. The AFM force measurement results showed that the adhesion between the polymers and model coal surface increased with increasing the KCl concentrations due to the compressed electric double layer, and the average adhesion of PAM was about one order of magnitude smaller than that of HMPAM. Such difference was mainly ascribed to the hydrophobic attraction between the hydrophobic chain of HMPAM and model coal surface. Meanwhile, the attractive hydrophobic interaction between the hydrophobic chains induced the formation of multiple layers of HMPAM, which was in consistence with the QCM-D results. The fundamental insights into the interaction mechanisms of HMPAM/PAM on model coal surface will benefit the rational development of effective polymer additives for fine coal preparation.